Alongamento dos títulos de renda fixa no Brasil - Márcio G. P. Garcia; Juliana Salom\~ao (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2006)
– More than eleven years after the end of hyperinflation in Brazil, domestic bond markets have been unable to lengthen the average maturity of both public and private bonds. This paper shows that the lengthening is theoretically and practically (we analyzed the experiences of Israel, Mexico and Poland), a consequence of persistent stabilization programs that successfully reduced systemic risk. Therefore, it is pointless to try to achieve the lengthening as an objective in isolation. It is necessary to improve the economic fundamentals that maintain a high level of systemic risk. Only in this context, measures that aim at lengthening bonds' maturity will indeed produce positive results.
Keywords: E43; E44; F34; H63; G15; 330; Rentenmarkt; Öffentliche Anleihe; Brasilien